Dynamics of Peroxisome Homeostasis and Its Role in Stress Response and Signaling in Plants - Su, Tong; Li, Wenjing; Wang, Pingping; Ma, Changle (Frontiers in Plant Science, 2019)
Peroxisomes play vital roles in plant growth, development, and environmental stress response. During plant development and in response to environmental stresses, the number and morphology of peroxisomes are dynamically regulated to maintain peroxisome homeostasis in cells. To execute their various functions in the cell, peroxisomes associate and communicate with other organelles. Under stress conditions, reactive oxygen species produced in peroxisomes and other organelles activate signal transduction pathways, in a process known as retrograde signaling, to synergistically regulate defense systems. In this review, we focus on the recent advances in the plant peroxisome field to provide an overview of peroxisome biogenesis, degradation, crosstalk with other organelles, and their role in response to environmental stresses.